Alcoholism and mortality in Eastern Europe - Evgeny Yakovlev (IZA World of Labor, 2021)
Eastern European countries, particularly former Soviet Union economies, traditionally have the highest rates of alcohol consumption in the world. Consequently, they also have some of the highest male mortality rates in the world. Regulation can be effective in significantly decreasing excessive drinking and its related negative effects, such as low labor productivity and high rates of mortality. Understanding the consequences of specific regulatory measures and what tools should be used to combat excessive alcohol consumption is essential for designing effective policies.
Keywords: P2; 330; alcohol consumption; mortality; labor productivity